Quantification and use of food losses: the case of cantaloupe melon in a region of North-Central Mexico - Espinoza-Arellano, José de Jesús; Fabela-Hernández, Adriana Montserrat; Gaytán-Mascorro, Arturo; Reyes González, Arturo; Sánchez-Toledano, Blanca Isabel (Revista Mexicana de Ciencias Agrícolas, 2023)
According to FAO, about one-third of global food production is lost or wasted. This waste reduces the availability of foods for the population, increases their prices and generates problems of environmental pollution. A common problem in developing countries is the scarcity of data on the quantity, causes and uses of food losses. In this work, the quantification, by sowing stages, of the losses of cantaloupe melon, their causes and uses in the links of production, packaging and transportation in a region of North-Central Mexico known as the Comarca Lagunera was carried out. This region is the largest producer of cantaloupe melon in Mexico, with an area of more than 4 565 ha and a production of 165 663 t. A structured questionnaire was applied in person to a statistical sample of 47 producers and eight packers. It was found that losses, both in production and packaging, vary according to the sowing stage, with greater losses in late sowings, followed by early and intermediate sowings. The main causes of losses are inadequate fruit size (small or very large), deformed, overripe, spotted and cracked. The product that is wasted in the orchard is destined to feed domestic animals or as fertilizer to the land; while the one that is discarded in the packaging centers is resold to small local intermediaries for commercialization and for the feeding of domestic animals.